2008
DOI: 10.1038/ncb1770
|View full text |Cite
|
Sign up to set email alerts
|

p53 mRNA controls p53 activity by managing Mdm2 functions

Abstract: The E3 ubiquitin ligase Mdm2 is a focal regulator of p53 tumour suppressor activity. It binds p53, promoting its polyubiquitination and degradation, and also controls p53 synthesis. However, it is not known how this dual function of Mdm2 on p53 synthesis and degradation is achieved. Here we show that the p53 mRNA region encoding the Mdm2-binding site interacts directly with the RING domain of Mdm2. This impairs the E3 ligase activity of Mdm2 and promotes p53 mRNA translation. We also show that introduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
264
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(276 citation statements)
references
References 29 publications
5
264
0
7
Order By: Relevance
“…39 p53-MDM2 protein interactions are well documented in the 40,45 MDM2 protein also binds to the coding region of p53 IRES RNA and promotes translation of the full-length p53 and the alternatively translated product Δ40p53. 12,35 p53 is also known to have RNA re-annealing properties, binding to the 5′UTR of its own mRNA, 34 as well as of Cdk4 46 and FGF2. 47,48 Recent reports showed that SMAR1 forms a ternary complex with p53-MDM2, in which MDM2 binds to residues 17-26 of p53 and SMAR1 binds to residues 14-16 of p53, with a simultaneous interaction of SMAR1 and MDM2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 p53-MDM2 protein interactions are well documented in the 40,45 MDM2 protein also binds to the coding region of p53 IRES RNA and promotes translation of the full-length p53 and the alternatively translated product Δ40p53. 12,35 p53 is also known to have RNA re-annealing properties, binding to the 5′UTR of its own mRNA, 34 as well as of Cdk4 46 and FGF2. 47,48 Recent reports showed that SMAR1 forms a ternary complex with p53-MDM2, in which MDM2 binds to residues 17-26 of p53 and SMAR1 binds to residues 14-16 of p53, with a simultaneous interaction of SMAR1 and MDM2.…”
Section: Discussionmentioning
confidence: 99%
“…3 This PTB-mediated control of p53 IRESs has been recently found to play a role in the p53-fibrillarin-rRNA methylation network. 9,10 Single-nucleotide polymorphisms in p53 5'UTR 11 or in the coding region of p53 IRES 7,11,12 decreased p53 IRES activity by altering PTB, MDM2 or hnRNPC1/C2 interactions with this regulatory region in p53 mRNA. Annexin A2 and PTB-associated splicing factor (PSF) proteins, putative p53 ITAFs, interact with p53 IRESs ex vivo in a stress-induced manner, showing greater association with the IRESs on thapsigargin treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The half-life of the protein is decreased in the absence of any stress and the proteasome inhibitor lactacystin restores p53 induction in response to a genotoxic stress. The RING domain-containing protein MDM2 ubiquitinates p53 C-terminus, promotes its degradation by the 26S proteasome and can also affect P53 mRNA translation (Candeias et al, 2008). MDM2 was found overexpressed both in Ba/F3 cell lines and primary cells expressing JAK2 V617F .…”
Section: Discussionmentioning
confidence: 99%
“…The TP53 pathway is crucial for tumour suppression, acting through regulation of cell-cycle control, apoptosis, senescence and DNA repair. The TP53 gene and its negative regulator MDM2 are central to this pathway, promoting polyubiquitination and degradation of TP53, and also controlling the TP53 synthesis (Toledo and Wahl, 2006;Candeias et al, 2008). Inactivation of the TP53 pathway has an important role in BRCA1-and BRCA2-associated tumourigenesis.…”
mentioning
confidence: 99%